On Trio Ternary ðšª-Semigroups - Vasantha, M; Madhusudhana Rao, D; Satish, T (International Journal of Engineering and Technology, 2018)
In this paper the terms trio L-trio TÎ“-ideal, La-trio TÎ“-ideal, R-trio TÎ“- ideal and trio TÎ“- ideal of a TÎ“-semi group are introduced and some examples are given. It is proved that (1) a TÎ“-semi group T is a trio TÎ“-semi group if and only if xÎ“TÎ“T = TÎ“TÎ“x = TÎ“xÎ“TÂ  for all x âˆˆ T, (2) Every trio TÎ“-semi group is a duo TÎ“-semi group, (3) Every commutative TÎ“-semi group is a trio TÎ“-semi group (4) Every quasi commutative TÎ“-semi group is a trio TÎ“-semi group.Â